Valuing worship images and church restoration actions in Huarás, Recuay and Aija (Ancash, Peru, Sixteenth - Twentieth Centuries) [Valoración de imágenes de culto y acciones de restauración en iglesias de Huarás, Recuay y Aija (Ancash, Perú, siglos XVI - XX)] - González Quijano, Álvaro (2014)
ABSTRACT This research focused on the impacts of discourses on images and, in turn, on the impact of these images on actions. Specifically, on the restoration actions conditioned by an image of secularization facing an autonomy discourse. For this purpose, analysis categories were defined: discourses, images and actions. Subsequently, discourse types were identified: heteronomy and autonomy; then, the type of images: worship and secular. And finally, the types of actions: restoration and new works. As a result of the analysis, a power relationship between discourses and images was established, projected by people with some type of power, which further inspired restoration actions, and the discourses and images projected by those affected by such actions.